Nuclear weapons and alliance institutions in the era of President Trump. Issue 1 (2nd January 2017) - Frühling, Stephan; O'Neil, Andrew
ABSTRACT: The swearing in of Donald Trump as the 45th President of the United States presages, at the very least, a period of flux in American strategy with respect to the relationship between nuclear weapons and alliances. In this response to three thoughtful rejoinders to our article, "Nuclear weapons, the United States and alliances in Europe and Asia: Toward an institutional perspective, " we clarify key aspects of our argument and discuss why alliance institutions are likely to be relatively robust in the face of change, how they can influence national decision-making, and argue that they may exert a moderating influence over the new administration.